How Taxes and Spending on Education Influence Economic Growth in Poland - Michał Konopczyński (Contemporary Economics, 2014)
This paper investigates the relationship between economic growth in Poland and four types of taxes and human capital investment. We primarily rely on an exogenous growth model that merges the Mankiw-Romer-Weil model, augmented with learning-by-doing and spillover-effects, with selected elements from the literature on optimal taxation. We demonstrate that in the period 2000- 2011, economic growth in Poland was primarily due to a rapid increase in the human capital stock (at a rate of 5% per annum) and only secondarily due to the accumulation of productive capital (2.7% annually). Simulations of tax cuts suggest that income taxes and consumption taxes restrict economic growth equally heavily. Simultaneously reducing all tax rates by 5 percentage points (pp) in Poland should increase annual GDP growth by approximately 0.4 pp. Increasing spending on education by 1 pp of GDP would increase the growth rate by approximately 0.3 pp.
Keywords: E62; H21; H52; 330; fiscal policy; income taxes; labor taxes; capital taxes; VAT; economic growth; human capital